2008
DOI: 10.1128/jcm.02029-07
|View full text |Cite
|
Sign up to set email alerts
|

Severe Necrotizing Fasciitis in a Human Immunodeficiency Virus-Positive Patient Caused by Methicillin-Resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a rarely reported cause of necrotizing fasciitis. We report an unusually severe case of MRSA necrotizing fasciitis in a previously undiagnosed AIDS patient. Molecular analysis revealed that the strain had the USA300/spa1 genotype, now an abundant cause of community-acquired MRSA infection. CASE REPORTA 36-year-old Hispanic male with no previously recognized significant medical conditions presented to the emergency department (ED) of an outlying community ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
(52 reference statements)
3
19
1
1
Order By: Relevance
“…We found that 57% of HIV-associated NF hospitalizations required ICU care. Use of ICU was mentioned in 4 patients described in prior case reports of HIVassociated NF [7,8,11,13]. Our findings are similar to those reported by Widjaja et al [27] and Das et al [24], showing need for ICU care in 63% and 56% of their patients, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…We found that 57% of HIV-associated NF hospitalizations required ICU care. Use of ICU was mentioned in 4 patients described in prior case reports of HIVassociated NF [7,8,11,13]. Our findings are similar to those reported by Widjaja et al [27] and Das et al [24], showing need for ICU care in 63% and 56% of their patients, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…The site of infection was described inconsistently in case reports of NF in HIV-infected patients. Two case reports indicated NF involving limbs [5,13], while cervical infection was described in 3 patients [7,10,11], and breast involvement in one [14]. While the small number of patients precludes meaningful analysis, the available data from these cases suggest involvement of uncommon body sites in patients with HIV-associated NF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations